Inhibitory Control as a Core Process of Creative Problem Solving and Idea Generation from Childhood to Adulthood. Issue 151 (March 2016) - Cassotti, Mathieu; Agogué, Marine; Camarda, Anaëlle; Houdé, Olivier; Borst, Grégoire
Abstract: Developmental cognitive neuroscience studies tend to show that the prefrontal brain regions (known to be involved in inhibitory control) are activated during the generation of creative ideas. In the present article, we discuss how a dual‐process model of creativity—much like the ones proposed to account for decision making and reasoning—could broaden our understanding of the processes involved in creative ideas generation. When generating creative ideas, children, adolescents, and adults tend to follow "the path of least resistance" and propose solutions that are built on the most common and accessible knowledge within a specific domain, leading to fixation effect. In line with recent theory of typical cognitive development, we argue that the ability to resist the spontaneous activation of design heuristics, to privilege other types of reasoning, might be critical to generate creative ideas at all ages. In the present review, we demonstrate that inhibitory control at all ages can actually support creativity. Indeed, the ability to think of something truly new and original requires first inhibiting spontaneous solutions that come to mind quickly and unconsciously and then exploring new ideas using a generative type of reasoning.